Komparasi Deversitas Moluska Musim Hujan dan Kemarau Di Kawasan Mangrove Luppung, Kabupaten Bulukumba - Magdalena Litaay; Like Ayu Sutrisnu; Andi Rahmawati; Nurul Istiqamah; Aryuni Utariningsih; Ayub Wirabuana Putra (Jurnal Kelautan Tropis, 2023)
This study aims to determine the diversity of molluscs (bivalves and gastropods) in two seasons in the mangrove ecosystem in Luppung, Ujung Loe District, Bulukumba Regency. Data collection usied random plot size I x m2, which applied at six stations determined by Purposive Sampling Method. Species Identification based on morphological characteristics and some other identification references. Data analysis including diversity, uniformity and dominance. The degree of similarity amongst station was analysed using Clustering by the Bray-Curtis method. Data analysis used the PAST 4.03. In this studi, 37 species of molluscs, consisting of the bivalve class (19 species) and the gastropod class (17 species) were identified. Bivalve Tellina (Quidnipagus) palate (Iredale, 1929) and GastropodsNassarius (Plicarcularia) leptospirus (A. Adams, 1852) were found at all six research stations. SpeciesCorbicula japonica (Prime, 1864). Uncertain Nerita (from the bush, 1844), Oualaniense Clithon (Lesson, 1831), Episcomitra cornicula (Linnaeus, 1758), Rough coastlines (Linnaeus, 1758), Pugilina cochlidium (Linnaeus, 1758), Melanoides punctata (Lamarck, 1822), Polinices mammilla (Linnaeus, 1758),and Rhinoclavis aspera (Linnaeus, 1758) found only in one station. The frequency of appearance of this type of mollusk shows the distribution of this type in the study location. The highest diversity Bivalvia is found at station 1 during the dry season and station 2 during the rainy season. The highest Gastropod diversity values were found at station 3 during the dry season and station 1 during the rainy season. Diversity of Bivalvia and Gastropods is higher in the dry season. There is no similarity in the structure of the gastropod community between the dry and rainy seasons. There is little similarity in bivalve community structure between the dry and rainy seasons.   Penelitian ini bertujuan untuk mengetahui keanekaragaman moluska (bivalvia dan gastropoda) pada dua musim di ekosistem mangrove di Dusun Luppung Kecamatan Ujung Loe Kabupaten Bulukumba. Pengambilan data menggunakan metode plot acak dan stasiun ditentukan dengan Purposive Sampling Method. Enam plot berukuran 1 x 1 m2 diaplikasi pada enam stasiun. Identifikasi species berdasarkan karakteristik morfologi dan disesuaikan dengan referensi identifikasi. Analisis data meliputi keanekaragaman, keseragaman, dan dominansi. Tingkat kesamaan (similaritas) antar stasiun menggunakan analisis Clustering metode Bray-curtis, Analisis data menggunakan Aplikasi PAST 4.03. Pada studi ini, Teridentifikasi 37 species (jenis) moluska, terdiri dari dua klas bivalvia (19 species) dan Gastropoda (17 species). Bivalvia jenis Tellina (Quidnipagus) palatam (Iredale, 1929) dan Gastropoda jenis Nassarius (Plicarcularia) leptospirus (A. Adams, 1852) dijumpai pada semua stasiun penelitian. Species Corbicula japonica (Prime, 1864). Nerita incerta (von dem Busch, 1844), Clithon oualaniense (Lesson, 1831), Episcomitra cornicula (Linnaeus, 1758), Littoraria scabra (Linnaeus, 1758), Pugilina cochlidium (Linnaeus, 1758), Melanoides punctata (Lamarck, 1822), Polinices mammilla (Linnaeus, 1758), dan Rhinoclavis aspera (Linnaeus, 1758) hanya di temukan di salah satu stasiun penelitian. Frekuensi pemunculan jenis moluska menunjukan sebaran jenis tersebut di lokasi penelitian. Nilai keanekaragaman tertinggi Bivalvia terdapat di stasiun 1 pada musim Kemarau dan stasiun 2 pada musim Hujan. Nilai keanekaragaman tertinggi Gastropoda terdapat di stasiun 3 pada musim Kemarau dan stasiun 1 pada musim Hujan. Keanekaragaman Moluska (Bivalvia dana Gastropoda) lebih tinggi pada musim Kemarau. Tidak terdapat kesamaan struktur komunitas gastropoda antara musim kemarau dan hujan. Terdapat sedikit kesamaan struktur komunitas bivalvia antara musim kemarau dan hujan.